Building Tolerance Values on the Religious Groups in Islam Based on Intellectual Ta'aruf - Rohman, Abdul (International Conference of Moslem Society, 2018)
The relation in groups within the Muslims is often constrained by the fanatic passion of the members. This is because of the influence of their scholars, teachings and ideology, so that their relationships are limited, exclusive and rigid. The purpose of this article is to provide an offer through the application of intellectual ta'aruf (knowing each other) to all groups in Islam, so that it can provide an objective awareness to all members about the importance of building inter-group relationships in order for Muslims’ unity to be maintained. The Islamic teachings recognize the existence of diverse groups, because their existence is a necessity. However, the existence of the groups should know each other, which is not only based on a mere physical introduction, but it can be better if the introduction is based on elements of intellectualism, thus bringing the form of human consciousness that cannot be separated from the divine values. The intellectual ta'aruf is a means and media relation that can be used as a method to encourage group followers in Islam to be a tolerant, moderate and inclusive society. In this ta'aruf concept, people are expected to be aware of the reason toward the formation of groups, it has high adhesiveness, fanatics, and obstacles in an effort to understand the doctrine carried out by a group that is different from them. If this intellectual ta’aruf can become the basic for each group, they can certainly build the relationships between groups with a comfortable, open, moderate and solid, although they still maintain the habits and characters that live in their respective groups.